Parental involvement in supporting their children in inclusive education: Cooperation with school professionals in Finland - Koskela, Teija; Sinkkonen, Hanna-Maija (Cogent OA, 2025)
This paper deals with the experiences of parents participating in meetings or other discussions at schools where their children’s support for learning is planned. In inclusive education, cooperation between school and home should be a confidential relationship. Despite intentions to develop legislation and practices for home–school collaboration, the system does not appear to be robust because in the realization of the support varies between schools and districts. In this study, phenomenographic approach was used to reveal how the experiences of the interviewed parents varied. The context of research is Finnish elementary school attended by students aged 7–15. Altogether, 11 interviews with parents of students with need of support were conducted. In this study, we present four types of experiences of parental involvement: equal partners, satisfied followers, active opponents, and cynical defendants. The parents reported experiences of fluent cooperation situations and confidential relationships with school personnel, but the quality of cooperation was not consistent. This finding indicates that attention should be paid to developing the practices to enhance collaboration and interactional skills among school personnel working with parents so that reciprocal confidence can be reached.